EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN QUANTUM TEACHING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DI KELAS II PATAYAT PONDOK PESANTREN MUSTHAFAWIYAH PURBA BARU - Ummawiyah Hasibuan; Eva Yanti Siregar; Roslian Lubis (JURNAL MathEdu (Mathematic Education Journal), 2020)
Abstract The aimof this studyis to know whether the use of quantum teaching is effective on students’ mathematical problem solving ability at the second Patayat Pondok Pesantren Musthafawiyah Purba Baru. The research was conducted by applying experimental method (one group pretest post test design) with 48 students as the sample and they were taken by using cluster random sampling technique. Observation and test were used in collecting the data. Based on descriptive analysis, it was found: (a) the average of using quantum teaching was 3.5 (good category) and (b) the average of students’ mathematical problem solving ability before using quantum teaching was 46.62 ( fair category) and after using quantum teaching was 78.74 (good category). Furthermore, by using pair sample ttest(SPSS 22), the result showed the significant value was less than 0.005 (0.000<0.005).It means,the use of quantum teaching is effective on students’ mathematical problem solving ability at the second Patayat Pondok Pesantren Musthafawiyah Purba Baru